Spread of eimeriosis among calves under the conditions of south European part of Russia - N. T. Safiullin (Российский паразитологический журнал, 2019)
The purpose of the research: to define the degree of spread of eimeriosis among calves under the conditions of south European part of Russia. Materials and methods. The researches were carried out in 11 entities of Krasnodar Territory, Stavropol Territory and Rostov Region in 2016-2017. The material for the researches was fecal specimen of cattle from entities of different forms of ownership. Total of 975 fecal specimen of cattle were studied. Fecal specimens were studied according to Fulleborn’s method. Invasion extensiveness (IE, %) and average number of oocysts in 1 g of feces were determined. Seasonal dynamics of infection of young stock cattle was studied by studies of fecal specimens of 38 heads in January - February, 43 heads in March - May, 64 heads during summer and 55 heads during autumn period. Influence of the stock density of calves in a pen on infection by eimeria was studied on 249 calves, among which 62 animals were kept in individual pens, 25 animals were kept in a pen for 2-5 animals, 28 calves were kept in a pen for 6-10 animals, 55 calves were kept in a pen for 11-15 animals and 75 calves were kept in a pen for 16 animals and more. Fecal specimens were studied three times. Obtained results were processed statistically. Results and discussion. Animals were infected by eimeria regardless of the type of entity. Average infection of the cattle in all tested entities was 47.43% when 180.5±8.3 samples of oocysts were found in average in 1 g of feces. In entities the infection of young stock cattle varied from 0 to 100% with maximum result at Urozhaynoe CJSC of Stavropol Territory when 362.3±9.7 samples of oocysts were found in 1 g of feces. To the fullest extent calves were infected by eimeria at the age of 3-4 months (IE 70.73%) when 364.3±8.2 samples of oocysts were found in 1 g of feces in average. Mature animals were infected minimally (IE 20.0%). Maximum animal infection was in spring and in autumn, 53.49% and 61.81% respectively when 282.3±7.5 and 324.6±8.3 samples of oocysts were available in 1 g of feces. It was established, that while rising the stocking rate of calves in the pen the eimeria infection also greatly increases. Minimal invasion was in calves which were kept in individual pens.